The legend of Sleepy Hollow - Irving, Washington, 1783-1859.; Rackham, Arthur, 1867-1939 (New York : Books of Wonder, 1990)
Illustrations by Arthur Rackham accompany this retelling of Irving$1 (Bs classic tale of a headless horseman.s
Keywords: Ghosts -- Fiction; New York (State) -- History -- 1775-1865 -- Fiction